Conservadoras y Dogmáticas, Las Universidades se Transformaron en Iglesias - Sampietro, Eduardo (La Sociología en sus Escenarios, 2009)
Abstract. In hardly one week, throughout tight a series of conferences, seminaries and factories that had like scene different national universities from Capital and Gran Buenos Aires, one of the most important academic ones of the last decade in the field of social sciences congregated to several hundreds of students, educational and public in general with the objective to interchange opinions on salient aspects of the continental reality. Doctorate in Social and Economic Sciences in the German Federal Republic, Heinz Dieterich, titular professor in the Independent and Metropolitan University of Mexico, takes published more than 30 books on the Latin American confliction, the global society and the successive scientific and ideological paradigms that crossed to the century, among other many questions not less complex. With the formal excuse of the presentation of its last work “the crisis of the intellectuals in Latin America”, this German of Mexican birth but by adoption - critical furtive of Francis Fukuyama, his surroundings and its scriptwriters of turn talk during several days, in perfect Castilian, about so expensive questions to the idiosyncrasy of the towns like the popular education, the critical thought, the regional identities and the inalienable right of each nation to choose and to determine its own future. Resumen. En apenas una semana, a lo largo de una apretada serie de conferencias, seminarios y talleres que tuvo como escenario distintas universidades nacionales de Capital y Gran Buenos Aires, uno de los académicos más importantes de la última década en el campo de las ciencias sociales congregó a varios cientos de estudiantes, docentes y público en general con el objetivo de intercambiar opiniones sobre aspectos salientes de la realidad continental. Doctorado en Ciencias Sociales y Económicas en la República Federal Alemana, Heinz Dieterich, profesor titular en la Universidad Autónoma y Metropolitana de México, lleva publicados más de 30 libros sobre la conflictividad latinoamericana, la sociedad global y los sucesivos paradigmas científicos e ideológicos que cruzaron al siglo, entre otras muchas cuestiones no menos complejas. Con la excusa formal de la presentación de su última obra "La crisis de los intelectuales en América latina", este alemán de nacimiento pero mexicano por adopción -crítico furtivo de Francis Fukuyama, su entorno y sus guionistas de turno- se explayó durante varias jornadas, en perfecto castellano, acerca de cuestiones tan caras a la idiosincrasia de los pueblos como la educación popular, el pensamiento crítico, las identidades regionales y el derecho inalienable de cada nación a elegir y determinar su propio futuro.